Initial management of postpartum hemorrhage: A cohort study in Benin and Mali. Issue 1 (November 2016) - Tort, Julie; Traoré, Mamadou; Hounkpatin, Benjamin; Bodin, Cécile; Rozenberg, Patrick; Dumont, Alexandre
Abstract: Objective: To determine the components of initial management associated with a decreased risk of severe postpartum hemorrhage (PPH) in Benin and Mali. Methods: A cohort study was conducted between May 2013 and September 2014 that included all women who delivered vaginally in seven participating centers and who presented excessive bleeding after birth. Severe PPH was defined as PPH that required surgical treatment (vascular ligature and/or hysterectomy), and/or blood transfusion, and/or transfer to an intensive care unit, and/or an outcome of maternal death. Logistic regression was used to identify the components of initial PPH management that were associated with severe PPH, adjusting for case mix. Results: A total of 223 women presented a primary PPH presumably caused by uterine atony. Among those, 88 (39.5%) had severe PPH. Nearly one-third of women (30.4%) had a late injection of oxytocin (> 10 minutes) after PPH diagnosis or no injection. Oxytocin injection within 10 minutes after the PPH diagnosis was significantly associated with a decreased risk of severe PPH (adjusted OR = 0.3; 95% CI, 0.14–0.77). Conclusion: Decrease in the delays in oxytocin administration is a key determinant to improve maternal outcomes related to PPH in this context.